2023
DOI: 10.1039/d3se00043e
|View full text |Cite
|
Sign up to set email alerts
|

Modeling future hydrogen supply chains in the western United States under uncertainties: an optimization-based approach focusing on California as a hydrogen hub

Abstract: With a vibrant economy and regulatory drivers to decarbonize, California could be a major hydrogen demand center, but uncertainties in hydrogen demand, supply, and government policy can influence infrastructure deployment....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In an examination of research in [54], the projections for 2050 for both the supply and consumption of hydrogen vary widely. Figure 8a shows hydrogen global demand; it has been reported that, even with uncertainties, hydrogen demand increases according to [94] as shown Figure 8b. Research by [48] reported hydrogen energy demand using four scenarios.…”
Section: Hydrogen Energy Supply and Demand Dynamicsmentioning
confidence: 89%
“…In an examination of research in [54], the projections for 2050 for both the supply and consumption of hydrogen vary widely. Figure 8a shows hydrogen global demand; it has been reported that, even with uncertainties, hydrogen demand increases according to [94] as shown Figure 8b. Research by [48] reported hydrogen energy demand using four scenarios.…”
Section: Hydrogen Energy Supply and Demand Dynamicsmentioning
confidence: 89%
“…In a similar vein, storage techniques (T) are tank (TA), cylinder (CY), and salt caverns (SC) based on Vishal et al (2023). These products are distribution (DIS) by pipeline (PL) and truck (TRK) (Vijayakumar et al, 2023). Yue et al (2021) conclude transportation (TP), industries (ID), and residential (RE) as end user (EU) for hydrogen.…”
Section: Hydrogen Supply Chain Downstream (Hscd) Componentsmentioning
confidence: 99%